Enhanced Polysulfide Conversion with Highly Conductive and Electrocatalytic Iodine‐Doped Bismuth Selenide Nanosheets in Lithium–Sulfur Batteries. (23rd March 2022) - Li, Mengyao; Yang, Dawei; Biendicho, Jordi Jacas; Han, Xu; Zhang, Chaoqi; Liu, Kun; Diao, Jiefeng; Li, Junshan; Wang, Jing; Heggen, Marc; Dunin‐Borkowski, Rafal E.; Wang, Jiaao; et al.
Abstract: The shuttling behavior and sluggish conversion kinetics of intermediate lithium polysulfides (LiPS) represent the main obstacles to the practical application of lithium–sulfur batteries (LSBs). Herein, an innovative sulfur host is proposed, based on an iodine‐doped bismuth selenide (I‐Bi2 Se3 ), able to solve these limitations by immobilizing the LiPS and catalytically activating the redox conversion at the cathode. The synthesis of I‐Bi2 Se3 nanosheets is detailed here and their morphology, crystal structure, and composition are thoroughly. Density‐functional theory and experimental tools are used to demonstrate that I‐Bi2 Se3 nanosheets are characterized by a proper composition and micro‐ and nano‐structure to facilitate Li + diffusion and fast electron transportation, and to provide numerous surface sites with strong LiPS adsorbability and extraordinary catalytic activity. Overall, I‐Bi2 Se3 /S electrodes exhibit outstanding initial capacities up to 1500 mAh g −1 at 0.1 C and cycling stability over 1000 cycles, with an average capacity decay rate of only 0.012% per cycle at 1 C. Besides, at a sulfur loading of 5.2 mg cm −2, a high areal capacity of 5.70 mAh cm −2 at 0.1 C is obtained with an electrolyte/sulfur ratio of 12 µL mg −1 . This work demonstrated that doping is an effective way to optimize the metal selenide catalysts in LSBs. Abstract : An innovative sulfur host, based on an iodine doped bismuth selenide (I‐Bi2 Se3 ), is demonstrated as a multifunctional polysulfide mediator by immobilizing the LiPS and catalytically activating the redox conversion. The promoted adsorption capacity and catalytic effect are confirmed by experiments and theoretical calculations; thus, batteries with exceptional lifespan are delivered.